Implementasi GIS Dan Metode MOORA Dalam Pemetaan Dan Pemilihan Lokasi Terbaik Penanaman Pohon - Nora Asyiqin; Triase (Universitas Budi Darma, 2026)
Amid rapid technological advancement, the use of digital systems such as Geographic Information Systems (GIS) plays a crucial role in enhancing the effectiveness of environmental conservation programs by enabling spatial analysis and efficient determination of suitable tree-planting locations. KSE UINSU (Karya Salemba Empat, State Islamic University of North Sumatra) annually conducts tree-planting activities involving hundreds of students across various regions in Indonesia, particularly in areas requiring reforestation, such as degraded land, flood-prone zones, coastal abrasion areas, and landslide-prone regions, including the City of Medan and Deli Serdang Regency. However, previous practices in location selection were often carried out without adequate data, resulting in time-consuming field verification and uncertainty regarding land suitability, soil conditions, accessibility, and regional characteristics. Therefore, a more systematic and data-driven approach is required to support faster, more accurate, and measurable decision-making. This study adopts a quantitative approach by integrating Geographic Information Systems (GIS) and the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to identify the most suitable locations for tree planting in the City of Medan and Deli Serdang Regency